Cognitive Linguistics and Husserlian Phenomenology - Soledad González, Daniela (2018)
Several scientific disciplines have attempted to answer questions likeWhat is the meaning of thought? and How do we think? Psychology and Linguistics are some of them. This paper attempts to establish some contributions of Husserlian Phenomenology to Cognitive Linguistics, in relation to the theory of knowledge and meaning, mainly. First, Husserl’s ideas will be reviewed, based on his Logical Investigations. Secondly Cognitive Linguistics will be presented as an analysis perspective of linguistic phenomena characterized by a particular conception of human mind. Then, some correspondences between the two theoretical approaches will be pointed out. Finally, a brief conclusion will be presented.